Pembelajaran Berdiferensiasi Melalui Sitrasic - Lestari, Dewi (Universitas Mathla'ul Anwar Banten, 2024)
The difference in learning in TK Negeri Pembina Purwantoro has various students who come from various regions outside Purwantoro, with various family backgrounds of education and work. So that the characteristics of students are also diverse. This study applies the sitrasic learning leadership program. The research method uses a pre-experiment with a one group pretest-posttest design type. The samples used were 2 classes, namely group A with 12 students and group B with 30 students. The difference test uses an independent sample t test. The results of the study showed that there were differences in student learning outcomes with the PBL learning method and student learning outcomes with the differentiated method through sitrasic.